2010
DOI: 10.1007/s11104-010-0660-3
|View full text |Cite
|
Sign up to set email alerts
|

Paenibacillus polymyxa SQR-21 systemically affects root exudates of watermelon to decrease the conidial germination of Fusarium oxysporum f.sp. niveum

Abstract: Paenibacillus polymyxa SQR-21 has been identified as a potential agent for the biocontrol of Fusarium wilt in watermelon, which is caused by the pathogenic fungus Fusarium oxysporum f.sp. niveum (FON). In the present study, the effects of root exudates from watermelon plants inoculated or noninoculated with either SQR-21 or FON on conidial germination of FON were investigated. Compared to the control, conidial germination was decreased with root exudates from SQR-21-inoculated plants, but conidial germination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 30 publications
3
50
0
Order By: Relevance
“…Organic acids such as oxalic acid, citric acid, ascorbic acid and malic acid are main components in root exudates (Ling et al 2011). Similarly, in the present study, oxalic acid and citric acid were detected in all the PGPR's treatments, including control plant root exudates.…”
Section: Organic Acid Composition Of Root Exudatessupporting
confidence: 81%
“…Organic acids such as oxalic acid, citric acid, ascorbic acid and malic acid are main components in root exudates (Ling et al 2011). Similarly, in the present study, oxalic acid and citric acid were detected in all the PGPR's treatments, including control plant root exudates.…”
Section: Organic Acid Composition Of Root Exudatessupporting
confidence: 81%
“…The rhizosphere of own-root watermelon also presented an over-representation of Bacilli (Fig. 4), which contained several well-known beneficial microbes, including Bacillus amyloliquefaciens (Xu et al 2013) and Paenibacillus polymyxa (Ling et al 2011). Further investigation also found some beneficial genera, such as Bacillus spp.…”
Section: Discussionmentioning
confidence: 96%
“…This may be because the ecologically relevant concentrations of PA were relatively low and insufficient to cause such inhibition. Recent studies have shown that many plant species resist potential soil-borne pathogens by modifying the amounts and composition of organic acids in their root exudates (Hao et al 2010;Kamilova et al 2006;Li et al 2013;Ling et al 2011;Pan et al 2013). Consequently, we believe that decreasing the colony growth and biomass of F. oxysporum by PA would be one of the mechanisms by which lily plants resist this pathogen.…”
Section: Discussionmentioning
confidence: 99%